Corporate Social Responsibility As a Moderating Variable on Financial Performance With Company Value - Sugeng Suroso (International Journal of Applied Finance and Business Studies, 2020)
This study aims to determine how the influence of financial performance on firm value with the disclosure of corporate social responsibility as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 – 2020. The sample of the study was 21 manufacturing companies listed on the IDX. Sampling from the population using the purposive sampling technique. The results of the study using multiple linear regression show that financial performance as a proxy for ROA has a significant positive effect on firm value, and corporate social responsibility disclosure can moderate the effect of ROA on firm value.